If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -4) + 8 = 6 Reorder the terms: 3(-4 + 2x) + 8 = 6 (-4 * 3 + 2x * 3) + 8 = 6 (-12 + 6x) + 8 = 6 Reorder the terms: -12 + 8 + 6x = 6 Combine like terms: -12 + 8 = -4 -4 + 6x = 6 Solving -4 + 6x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6x = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 6 + 4 6x = 6 + 4 Combine like terms: 6 + 4 = 10 6x = 10 Divide each side by '6'. x = 1.666666667 Simplifying x = 1.666666667
| 2x/3=(X-10)/4 | | 7w+14=14 | | 7w+14=4 | | 19-5x=-15 | | 11x+13=200 | | -5x+16=-54 | | 16m^2-81(m-3)(m-3)=0 | | 1+3x=-3+9x | | 3p+12=6p-24 | | 16=25 | | 5x-0.6x=7.48 | | 2.9=8.3x | | .5x=.4+.4x | | -6x+9x=-15 | | 12-3x=-8.7 | | 3.6(x+5)=50.4 | | w/4=w/2=1/4=W | | 2x^3+19x^2+38x-35=0 | | a+(a+3)+(a-5)=76 | | y+x=63 | | 5.1x-18=48.3 | | 0.70x=1 | | -4(x+12)=-60 | | 0.85x=1 | | 54x+3(x+30)+(x+30)*4+50=3493 | | T=7-3n | | 2*x-2*x=0 | | 6x-18 = 6 | | 2/×=10/15 | | 2*x-2*y=0 | | x-(x*0.325)=1870 | | x-(x*0.16)=1784 |